(untitled) (Journal of Environmental Science and Natural Resources, 2015)
This study was conducted to determine the contamination of E. coli and Salmonella for different types of foods in Chittagong city area. In case of laboratory examination, almost half (49.58%) of the samples were contaminated where 28.75% positive for E. coli. and 20.83% for Salmonella. The positive cases for type A sample was 20 out of 96 constituting 20.83% whereas the positive cases for type B sample was 49 out of 144 constituting 34.03% for E. coli. The positive cases of type A sample was 15 out of 96 making up 15.63% and for type B sample was 35 out of 144 making up 24.31% for Salmonella.A chi-square (?2) test was used to examine the equality of observed proportions for E. coli and Salmonella of each item of both types of food where significant difference among the observed proportion for E. coli (p-value<0.01) and Salmonella (p-value=0.032) for different items of A type and for E. coli (p-value<0.01) for different items of B type were observed and an odds ratio (OR) was measured for association between exposure and outcome where the probability of contaminated by E. coli of type B food is higher than contaminated of type A food (OR= 1.96 and CI:1.07-3.58). The probability of contaminated by Salmonella of type B food was higher than type A food (OR= 1.73 and CI: 0.89-3.39).The comparatively high bacteria in type B samples indicated contamination from water, practice of inadequate hygienic measures, mishandling, improper storage, inadequate cooking and above all unhygienic condition of the retail shops. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22033 J. Environ. Sci. & Natural Resources, 6(1): 11-14 2013